Analisis Minat Belajar Mahasiswa danTingkat Kehadiran Dosen Pengaruhnya terhadap Tingkat Kelulusan Mahasiswa Menggunakan Fuzzy Quantification Theory - Hindayati Mustafidah; Suwarsito Suwarsito (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2012)
Some studies mentioned that interest in learning has an impact on the achievement of student learning. The results of other studies mentioned that there is an influence of the presence of a lecturer in courses against graduation rates of students in courses. This study analyzes how its influence student learning interest in relation to the level of presence of a lecturer in courses of graduation rates of students in courses that are indicated by the percentage of the least B. This study uses Fuzzy Quantification Theory I (FQT) method. Based on the six sub indicators in the interest of learning i.e. 1) passion to learn, 2) initiatives in learning, 3) responsive in learning, 4) mind focusin learning, 5) the willingness to learn, and 6) hard work in learning, retrieved the results that students learning initiative contributes most in attendance rates of lecturer contributed in its effects on the achievement the percentage of the value of the graduation courses at least B compared with other sub indicators of interest in learning